The present value relation over six centuries: The case of the Bazacle company - le Bris, David; Goetzmann, William N.; Pouget, Sébastien (Journal of Financial Economics, 2019)
We study asset pricing over the longue durée using share prices and net dividends from the Bazacle company of Toulouse, the earliest documented shareholding corporation. The data extend from the firm’s foundation in 1372 to its nationalization in 1946. We find an average dividend yield of 5% per annum and near-zero long-term, real capital appreciation. Stationary dividends and stock prices enable us to directly study how prices relate to expected cash flows, without relying on a rate of return transformation. A reduced-form asset pricing model with persistent dividends and a time-varying risk correction is not rejected by the data.